First Report of Tomato Leaf Curl Cebu Virus Associated with Stachytarpheta jamaicensis Golden Yellow Mosaic Disease in Taiwan - Tseng, Yi-Wen (Plant disease, 2023)
Stachytarpheta jamaicensis (L.) Vahl, also known as snack weed, is an exotic plant in Taiwan. In April 2021, severe golden yellow mosaic leaves (Fig. S1) were observed on S. jamaicensis plants in Taichung City, Taiwan. Samples from eight symptomatic and two asymptomatic plants were collected from the public flowerbed. Total DNA was extracted from each of the collected samples by using a modified CTAB method (Echevarría-Machado et al. 2005). PCR with Begomovirus degenerate primers (PAL1v1978/PAR1c715; Rojas et al. 1993) was conducted. The expected 1.5-kb fragment was amplified only from the 8 symptomatic samples. Two randomly selected amplicons were cloned on pCRII-TOPO TA vector (Invitrogen Co., San Diego, CA, USA) and sequenced with the ABI3730 automatic sequencer (Applied Biosystems, Hammonton, NJ, USA) at National Chung Hsing University (NCHU). After NCBI BLASTn analysis, the sequences were shown to be most closely related to tomato leaf curl Cebu virus (ToLCCeV) isolates (EU487042, EU487025, KU946997), with 92.4-92.5% nucleotide sequence identity by using the CLUSTAL W method of MegAlign program (DNASTAR, Inc., Madison, WI, USA). A ToLCCeV specific primer pair (FJJ2021-165 /166 5'-ACTTACAGGCCCATGTATCG-3' / 5'-GAATGGGTATCCGAGCACG-3') was designed to amplify and sequence the remaining half of viral DNA. The expected 1.6-kb amplicon was amplified only from the symptomatic samples. The full-length of DNA-A consisted of 2.7-kb nucleotides (ToLCCeV isolate stachy, ON525110 and ON525111) and contained six open reading frames (two in viral sense, V1 to V2 and four in the viral complementary sense, C1 to C4) and the conserved nonanucleotide motif (TAATATTAC). The full-length DNA-A of ToLCCeV stachy isolates shared 99.9% nucleotide identity to each other and 91.2-92.4% and 91.3-92.5% nucleotide identities to other ToLCCeV isolates (EU487042, EU487025, KU946997) available in NCBI GenBank. Besides, ToLCCeV is a monopartite begomovirus that harbors no DNA-B. Thus, there were no bands amplified from the degenerate primer pair for DNA-B (DNABLC2 / DNABLV2; Green et al. 2001). Furthermore, the infectious clone was constructed by using phi29 DNA polymerase (New England Biolabs, Ipswich, MA, USA) for rolling circle amplification (RCA). The RCA product was partially digested with ApaI (NEB) and ligated into the binary vector pCambia0380 (AF234290). The resulting recombinant vector was transformed into Agrobacterium tumefaciens C58. A. tumefaciens C58, containing the infectious ToLCCeV-Stachy DNA-A vector, was grown overnight in LB broth containing kanamycine (50 μg/ml) at 28°C. S. jamaicensis and Nicotiana benthamiana (Nb, four to six leaf stage) plants were agroinoculated to confirm the infectivity of the ToLCCeV clone. The leaf curling and blister symptoms were observed on the Nb systemic leaves 17-day post inoculation (dpi) and the golden yellow mosaic symptom noticed on S. jamaicensis systemic leaves 30-dpi. The presence of the viral DNA in the inoculated plants was confirmed by PCR using the specific primer pair of ToLCCeV. To the best of our knowledge, this is the first report of the monopartite begomovirus, ToLCCeV, associated with golden yellow mosaic disease in S. jamaicensis in Taiwan. The existence of ToLCCeV might severely impact the tomato and pepper industry because they are the natural hosts of ToLCCeV (Tsai et al. 2011) and ToLCCeV may be transmitted by the whitefly, Bemisia tabaci, in Taiwan (Ko et al. 2005)